Protocol to develop a framework addressing barriers to utilization of elimination of mother- to -child transmission of HIV services among pregnant women and lactating mothers in Gauteng province - Ndivhuwo Mukomafhedzi; Takalani G. Tshitangano; Shonisani E. Tshivhase; Foluke C. Olaniyi (MethodsX, 2023)
Mother-to-child transmission of HIV remains the primary contributor to HIV infections in children, globally. Despite the progress made to reduce new HIV infections in children, barriers to utilization of the Elimination of Mother-to-Child Transmission service remain the bottleneck that affects the program's effectiveness. This study aims to develop a framework to address barriers to the utilization of the Elimination of Mother-to-Child Transmission of HIV services among pregnant women and lactating mothers in Gauteng province. A convergent parallel mixed methods design will be employed in phases. Phase 1(a) quantitative will be collected from pregnant women and lactating mothers to describe barriers associated with poor utilization of elimination of mother-to-child transmission services and a potential strategy to facilitate EMTCT utilization; phase 1(b) qualitative data will be collected to explore reasons for poor utilization of EMTCT services and perceived strategy to enhance women's utilization of elimination of mother-to-child transmission services. Quantitative data will be analyzed using Stata software version 14.0 and qualitative data will be analyzed thematically and then results will be integrated. Phase 2: will focus on the development of a framework; Phase 3: will validate the developed framework. The conclusion and recommendations will be based on the findings of the study.